2018
DOI: 10.1016/j.foreco.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Recognizing Amazonian tree species in the field using bark tissues spectra

Abstract: The identification of tree species in the field is often a subjective process and misidentifications cause many problems for forest management in the Amazon Forest. Near infrared spectra from dried leaves of herbarium specimens are able to distinguish species in tropical forests. However, toolsto improve species identification directly in the field are needed. In this study, we tested whether spectral reflectance of bark tissues (rhytidome and phloem) collected with a portable spectrometer in the field can be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 45 publications
(24 reference statements)
0
19
1
Order By: Relevance
“…Recent studies have shown the effectiveness of FT‐NIR spectroscopy in botanical species identifications (Durgante et al., 2013; Fan et al., 2010; Hadlich et al., 2018; Lang et al., 2017; Lang et al, 2015; Prata et al, 2018). The method has also been used in vertebrate and invertebrate studies (Almeida de Azevedo et al., 2019; Rigby et al., 2014; Rodriguez‐Fernandez et al., 2011; Vance et al., 2014, 2016) and may be a viable alternative to characteristics used in classical taxonomy as it is highly cost‐effective, rapid, and can be non‐destructive (Rodriguez‐Fernandez et al., 2011; Vance et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the effectiveness of FT‐NIR spectroscopy in botanical species identifications (Durgante et al., 2013; Fan et al., 2010; Hadlich et al., 2018; Lang et al., 2017; Lang et al, 2015; Prata et al, 2018). The method has also been used in vertebrate and invertebrate studies (Almeida de Azevedo et al., 2019; Rigby et al., 2014; Rodriguez‐Fernandez et al., 2011; Vance et al., 2014, 2016) and may be a viable alternative to characteristics used in classical taxonomy as it is highly cost‐effective, rapid, and can be non‐destructive (Rodriguez‐Fernandez et al., 2011; Vance et al., 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, previous studies have concluded that ignoring the contribution of woody tree parts of the canopy in imaging spectroscopy data (i.e., satellite images) may lead to less accurate estimates of, for example, chlorophyll (Verrelst et al 2010) and nadir-viewed canopy reflectance (Asner 1998). Knowledge of species-specific stem bark spectra can also be used in developing accurate tree species identification algorithms (e.g., machine learning classification models) (Hadlich et al 2018). Accurate classification models could be valuable in the future for the forest industry and the development of autonomous forestry machinery.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the high variability of bark spectra, and the absorption features that can be found in these groups could be attributed to a high diversity of trees in the region (Hilje et al, 2015). Higher variability of bark spectra associated with a high diversity of trees has also been reported in other forest communities (Hadlich et al, 2018).…”
Section: Spectral Features Of Lichens and Their Host's Barkmentioning
confidence: 69%